2006
DOI: 10.1002/rcm.2394
|View full text |Cite
|
Sign up to set email alerts
|

Rapid characterization of edible oils by direct matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry analysis using triacylglycerols

Abstract: Direct matrix-assisted laser desorption/ionization time-of-flight mass spectrometric (MALDI-TOFMS) analysis of solutions of edible fats/oils yielded spectra useful for their rapid differentiation and classification. Results also reflected the individual fatty acid components and their degree of unsaturation. After dissolution in hexane, MALDI-MS analysis revealed spectra showing characteristic triacylglycerols (TAGs), the main fat/oil components, as sodium adduct ions. The Euclidean distances calculated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
71
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 16 publications
6
71
0
2
Order By: Relevance
“…ESI-LTQ-Orbitrap MS is also used to compare analyses and confi rm levels of unsaturation. MALDI-TOF has been used for the rapid characterization of purifi ed edible oils based on the lipid fi ngerprint (18)(19)(20)(21)(22)(23), but the utility of this method with more complex algae lipid extracts has not been demonstrated. The method reported herein provides analysis of the TAG fi ngerprints of different algae species while circumventing the need to derivatize samples for fatty acid ester analysis or use specialized instruments.…”
Section: Esi-ltq-orbitrap Analysis Of Algal Lipid Extractsmentioning
confidence: 99%
“…ESI-LTQ-Orbitrap MS is also used to compare analyses and confi rm levels of unsaturation. MALDI-TOF has been used for the rapid characterization of purifi ed edible oils based on the lipid fi ngerprint (18)(19)(20)(21)(22)(23), but the utility of this method with more complex algae lipid extracts has not been demonstrated. The method reported herein provides analysis of the TAG fi ngerprints of different algae species while circumventing the need to derivatize samples for fatty acid ester analysis or use specialized instruments.…”
Section: Esi-ltq-orbitrap Analysis Of Algal Lipid Extractsmentioning
confidence: 99%
“…Using this protocol, it might be possible to monitor changes in the phospholipid ratios but not changes in TAGs. For some applications (and for lipidomicis studies), measurement of the relative changes of TAG as well as phospholipids is important (14)(15)(16).…”
Section: Downloaded Frommentioning
confidence: 99%
“…For example, Lay et al ( 15 ) demonstrated a rapid method for the analysis of edible oils by MALDI-MS that allowed determination of the relative abundances of TAGs with suffi cient accuracy to correctly identify blind-coded samples of various oils. Gidden et al ( 16 ) have also reported using MALDI-MS to rapidly differentiate Escherichia coli and Bacillus subtilis based on the phospholipid profi le and monitor changes in lipid content during the growth phases of the bacteria.…”
mentioning
confidence: 99%
“…In parallel, the nut oils were analyzed for their TAG composition using matrix-assisted laser desorption/ionization (MALDI)-MS combined with sophisticated data analysis. Monitoring of TAG profiles by MALDI-MS directly from whole plant oils and animal fats (TAG profiling) becomes increasingly popular [41][42][43][44] Table 1), detailed literature data concerning the TAG composition of many nut oil varieties using MALDI technology are not available so far.…”
Section: Introductionmentioning
confidence: 99%